Motif Ornamen Bali Sebagai Sumber Inspirasi Dalam Penciptaan Seni Lukis Wayang Kamasan - Adiguna, Made Hendra; Budiarta, I Dewa Putu Gede; Yugus, A.A Gede (Program Studi Seni Murni ISI Bali, 2022)
Wayang Kamasan painting is the main topic of thought in the creation of painting works of art, which were inspired by Balinese ornamental motifs. As for the research problems, namely: What are the Balinese ornamental motifs that are applied to the Wayang Kamasan form?, How to apply Balinese ornaments to the Wayang Kamasan form?, What techniques are used in creating paintings inspired by Balinese ornamental motifs?.The author conducted research on Balinese ornamental motifs as a source of inspiration in the creation of Wayang Kamasan painting through field research methods, with a source data source named Ni Wayan Sri Wedari, S.Sn who is the owner and leader of the Wasundari studio, with data collection techniques by observation, interviews and literature review. Art creation is carried out in stages (exploration, experimentation, and execution). Produce works of art with a tendency to contemporary style. The six works produced include: Arjuna Tapa, Sutasoma, Hanoman, Gugurnya Bisma, Lata Mahosadhi, and Kumbakarna.